The welfare of illegitimate children : a juristic analysis with special reference to Nur Salam - Muhamad Ilyas bin Mohd Mydin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
Illegitimate children are those born out of wedlock. This study examines their rights with special focus on a welfare home called Nur Salam / Yayasan Chowkit which take cares of illegitimate children in Chowkit, Kuala Lumpur. This study also looks at Nur Salam and its functions as a welfare home. The welfare and rights of illegitimate children are analyzed in the light of fiqh and local fatwÉ, and their positions are compared between Islamic Law and civil law. This research used qualitative methodology and included field work which involved gathering statistics and interviewing the stakeholders. This work demonstrates that these children should not be mistreated because they are not guilty for being illegitimate. Rather, the blame lies with the parents. In addition, in Islamic law there is no difference between legitimate children and illegitimate children, because every child is born innocent as is mentioned in the Prophetic tradition. These children should therefore be respected like all others and allowed to be leaders, judges, imÉm as well as witnesses. In other words, lineage should not restrict the opportunity of these children to hold any position in society, as every individual is judged by his personal deeds and not by those of his parents. As a matter of fact, being orphans, they should receive special attention. Islam puts great emphasis on treating orphans with love and sympathy. To conclude, this thesis suggests preventive measures as well as remedial measures. Preventive measures can ensure illegitimate births are reduced, while remedial measures are for the welfare of these children to assure that they get every right that others do in terms of respect in society, education and employment.